The Epstein–Barr virus nuclear protein SM is both a post-transcriptional inhibitor and activator of gene expression - Ruvolo, Vivian (The National Academy of Sciences, 1998)
The Epstein–Barr virus (EBV) nuclear protein BS-MLF1 (SM) is expressed early after entry of EBV into the lytic cycle. SM transactivates reporter gene constructs driven by a wide variety of promoters, but the mechanism of SM action is poorly understood. In this study, we demonstrate that the SM protein inhibits expression of intron-containing genes and activates expression of intron-less genes. We demonstrate that SM has the predicted inhibitory effect on expression of a spliced EBV gene but activates an unspliced early EBV gene. SM inhibited gene expression at the post-transcriptional level by preventing the accumulation of nuclear and cytoplasmic RNA transcripts. Conversely, SM led to increased accumulation of nuclear mRNA from intron-less genes without affecting the rate of transcription, indicating that SM enhances nuclear RNA stability. The ratio of cytoplasmic to nuclear polyadenylated mRNA was increased in the presence of SM, suggesting that SM also enhances nucleo-cytoplasmic mRNA transport. The degree of transactivation by SM was dependent on the sequence of the 3′-untranslated region of the target mRNA. Finally, we demonstrate that the amino-terminal portion of SM fused to glutathione-S-transferase binds radioactively labeled RNA in vitro, indicating that SM is a single-stranded RNA binding protein. Importantly, the latent and immediate-early genes of EBV contain introns whereas many early and late genes do not. Thus, SM may down-regulate synthesis of host cell proteins and latent EBV proteins while simultaneously enhancing expression of specific lytic EBV genes by binding to mRNA and modulating its stability and transport.